Expanding the Cultural Reach of Zoos - Alexandra Vaccaro; Jill Korach (Journal of Zoological and Botanical Gardens, 2025)
It is surprising that, despite focusing on delivering engaging and informative content to zoo and aquarium visitors nationwide, relatively few zoos or aquariums incorporate culture or the extensive species and place-based knowledge of local communities, also known as traditional ecological knowledge (or TEK). In an exploratory study of educational programming at the Wildlife Conservation Society’s five zoo and aquarium institutions, we found that only 15% of onsite signage, webpages, and in-person animal programs used cultural or TEK elements to educate visitors. The TEK presented was primarily limited to a place or cultural group’s name only or an image of native communities who live in the region where a particular species originated. We found little to no focus on providing more detailed accounts of the knowledge of the many different communities contributing to conservation at a local level. We conclude there are many opportunities for further research and for informal education facilitates to readily incorporate culture and TEK into existing exhibits and programming. Extending relationships with local native community members and integrating indigenous perspectives, among other strategies, can extend a zoo’s reach in novel ways.